The Scientific, Social, Environmental and Economic Value of N.E. Langkawi: An Overview of the Present Status - Noramly, Glenda; bin Hussin, Azhar; V. C, Chong,; Siew Moi, Phang, (Malaysian Journal of Science, 2005)
The area of North-east Langkawi is described, and the findings of the two scientific expeditions to Langkawi, where relevant to the north-east, are summarised. Threats to the environment and the potential of ecotourism in the area are discussed and the value of the conservation of this region of the Langkawi Islands is considered. Conclusions are that N .E. Langkawi has a physical landscape worthy of preservation, as well as a diverse and often unique biodiversity with interconnected ecosystems in a combination that has considerable commercial, scientific, social and educational value.